ANALISIS SIKAP KONSUMEN TERHADAP ATRIBUT SABUN MANDI (Studi Pada Sabun Mandi Merek Lux dan Giv Di Kota Malang) - Hence Izhar; Sumiati - -; Moeljadi P. - - (Sekolah Pascasarjana Universitas Brawijaya, 2010)
ABSTRACT Â The study has as its rationale the fact that there are numerousÂ brands of bath soap in the market. The changes of consumer behavior, which influenced by the economy crisis occurred in the Indonesia, has suppressed the producers to readjust their marketing programs. It is crucial for the firms to recognize the consumer attitudes on their marketing program. Moreover, consumer attitude is dominantly used in predicting the consumer behavior, in estimating the future demand of product, and in developing the appropriate marketing programs. The study aimed at understanding : (1). The consumer attitudes on the bath soaps (i.e, Lux and Giv brands) attributes, (2). The influence of the consumerâ€™s social environment toward the subjective norm in making the purchasing decisions on the Lux and Giv, (3). The differential of consumers attitudes on the Lux and Giv. Interview and questionnaire were used to collect data, by using the semantic differential scale method. Fishbein model and Wilcoxonâ€™s signed rank test were applied to the studyâ€™s results. The result of research indicate that : (1) There was a positive attitude of consumer on both the Lux and Giv. Attribute